Circular RNA Profiling Reveals That circRNA_104433 Regulates Cell Growth by Targeting miR-497-5p in Gastric Cancer - Wei, Weiyuan (Cancer Manag Res, 2020)
BACKGROUND: The role and mechanism of hsa_circRNA_104433 in gastric cancer (GC) are further elucidated. MATERIALS AND METHODS: CircRNA_104433 was selected by circRNA microarrays and GEO database. qRT-PCR was used to analyze the expression of circRNA_104433 in GC. The role of circRNA_104433 in GC cells was evaluated based on cell cycle progression, cell proliferation, cell apoptosis, and tumor xenograft experiment assay. To explore the mechanisms of circRNA_104433 in GC TCGA database, STRING version, qRT-PCR and luciferase assay were performed. Furthermore, the prognostic value of CDC25A in GC was determined based on the GEO database. RESULTS: The level of circRNA_104433 showed upregulation in GC tissues, and the expression of it showed a positive correlation with the degree of differentiation and the size of the tumor. Knockdown of circRNA_104433 inhibited cell cycle transition, and cell proliferation, while promoted cell apoptosis in GC. CircRNA_104433 directly binds to miR-497-5p, which directly regulates CDC25A. The median survival period of GC patients with high expression levels of CDC25A was 21.3 months, which was shorter than those with low group expression of CDC25A (35.9 months). The cell cycle proteins CDK1, CDK2, CCNB1, PKMYT1, CDC20, CHEK1 and CDC25A were coexpressed with CDC25A. CONCLUSION: These findings suggested that knockdown of circRNA_104433 expression suppressed tumor development in GC.